Antioxidative properties of eastern prickly pear (Opuntia humifusa) fermented with lactic acid bacteria and cell wall-hydrolyzing enzymes. (March 2020) - Quines-Lagmay, Venus C.; Jeong, Beom-Gyun; Kerr, William L.; Choi, Sung-Gil; Chun, Jiyeon
Abstract: Mucilaginous nature of Opuntia humifusa (Oh) cladodes complicates efficient extraction of bioactive compounds. To overcome this, Oh hydrolysates were prepared using cell wall-hydrolyzing enzymes (CHEs) and lactic acid bacteria (LAB) containing β-glucosidase activity. Treated Oh samples (at 37 °C for 60 h) include control-1 (LAB only, no enzyme), control-2 (no LAB, Viscozyme only), Oh-P (LAB+pectinase), Oh-C (LAB+cellulase), Oh-PC (LAB+pectinase+cellulase), Oh-V (LAB+Viscozyme), Oh-Px (LAB+Pectinex), and Oh-VPx (LAB+Viscozyme+Pectinex). On average, juice yields of fermented Oh samples were higher by 5% and 48% than those of control-2 and control-1, respectively. Total polyphenol contents increased by 71% in Oh-VPx. Total flavonoid contents of treated samples with CHE increased to an average 530.0 quercetin equivalent (QE)/mL after 60 h; value was four times higher than control-1 (121.99 QE/mL). Highest isorhamnetin content was in Oh-V (43.14 mg/mL). Flavonoid glycosides were gradually decreased, indicating release of flavonoid aglycone, isorhamnetin. DPPH* radical scavenging activity and reducing power increased by 58% and 98%, respectively, in Oh-VPx (14.06 μg GAE/mL and 113.75 μg GAE/mL, respectively). Hypoglycemic property of hydrolysates was also enhanced. This study shows that treatment with either β-glucosidase-active LAB or CHE might enhance the bioactivities of Oh, and combining the two might improve juice extraction and enhance bioactive properties. Highlights: Combined fermentation and enzyme hydrolysis enhanced Opuntia bioactive properties. Combined fermentation and enzyme hydrolysis improved Opuntia juice extraction. Hypoglycemic property was improved by combined fermentation and enzyme hydrolysis.